2016
DOI: 10.1016/j.psyneuen.2016.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in morning cortisol in youth at ultra-high-risk for psychosis

Abstract: Summary Research suggests abnormalities in hypothalamic-pituitary-adrenal (HPA) axis function play an important role in the pathophysiology of psychosis. However, there is limited research on the biological stress system in young people at ultra high risk (UHR) for psychosis. Morning cortisol levels are particularly relevant to study in this context, as these markers reflect HPA regulation. This is the first examination of sex differences in morning cortisol levels in UHR individuals. Twenty-eight UHR and 22 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…The results confirmed cortisol decline in the all-male sample of the present study. Blunted cortisol decline in healthy participants is characteristic of early life stressors ( Kuras et al, 2017 ) and is considered particularly maladaptive in males ( Carol et al, 2016 ). Furthermore, the results indicated that cortisol decline was independent of counting type.…”
Section: Discussionmentioning
confidence: 99%
“…The results confirmed cortisol decline in the all-male sample of the present study. Blunted cortisol decline in healthy participants is characteristic of early life stressors ( Kuras et al, 2017 ) and is considered particularly maladaptive in males ( Carol et al, 2016 ). Furthermore, the results indicated that cortisol decline was independent of counting type.…”
Section: Discussionmentioning
confidence: 99%
“…A better understanding of how cannabis use may be related to HPA dysfunction in UHR individuals could clarify inconsistencies as UHR individuals use cannabis at higher rates and frequency (Addington et al, 2014; Ksir and Hart, 2016), and the current results indicate that UHR individuals who use cannabis have higher cortisol levels. Future studies should also examine how cannabis use relates to other aspects of HPA axis function, as patients with schizophrenia experienced a flattened cortisol awakening response after cannabis exposure (Monteleone et al, 2014) and UHR individuals show blunted CAR and morning cortisol levels during the first hour after awakening in a home setting (Carol et al, 2016; Day et al, 2014). …”
Section: Discussionmentioning
confidence: 99%
“…Although our sample size is comparable to other studies conducted in the UHR population (Corcoran et al, 2012; Pruessner et al, 2013) and we controlled for age in our analysis, future studies with larger samples, and more power to control for multiple comparisons, should be conducted before any definitive conclusions are made. Larger studies should also examine sex-differences in cannabis use and cortisol levels as sex-differences in morning cortisol samples collected in home samples in UHR youth and in patients with schizophrenia have been reported (Carol et al, 2016; Pruessner et al, 2008). Additionally, while the current methods used to collect and analyze cortisol levels are consistent with previous examinations (Mittal and Walker, 2011; Walker et al, 2013), future studies that collect more cortisol samples across the day, especially the cortisol awakening response (CAR), and over consecutive days are needed to better understand cannabis use and the 24-hour circadian cycle of the HPA axis in UHR youth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cortisol awakening response could be significantly lower in males with FEP compared to male controls and affected females ( 11 ). Sex differences have also been suggested in morning cortisol levels in the at-risk stage ( 12 ). This moderating effect of sex might further be seen at the molecular level, on the glucocorticoid nuclear receptor NR3C1 , which acts as a transcription factor that binds to glucocorticoid response elements and regulates gene expression upon stress.…”
Section: Introductionmentioning
confidence: 99%